Heparin immobilization onto segmented polyurethaneurea surfaces―effect of hydrophilic spacers - 박기동; T. Okano; C. Nojiri; S. W. Kim (1988)
Heparin was immobilized onto segmented polyurethaneurea surfaces (Biomer) using hydrophilic poly(ethylene oxide) spacers of different chain lengths. The use of the hydrophilic spacer, poly(ethylene oxide), reduces protein adsorption and subsequent platelet adhesion on the surface. In addition, the bioactivity of the immobilized heparin is enhanced by the incorporation of these spacers. Immobilized heparin bioactivity is shown to be a function of PEO spacer length. Use of hydrophilic PEO spacers demonstrates that immobilized heparin's bioactivity is consistently higher than that of the C